Preliminary Studies on the N-Terminal Amino Acids of Human Plasminogen - Shulman, Sidney; Rifé, Ubaldo (Thrombosis and Haemostasis, 1961)
Human plasminogen has been analyzed for N-terminal amino acids. It was found to have one residue each of lysine and serine per molecule, with the possibility that threonine and glutamic acid may also serve in this role. On conversion to SK-plasmin, serine is lost as a terminal group and leucine appears as a new terminal unit.